Interpretasi Makna Leksikal dan Relaksional pada Term Yadd Pendekatan Sintagmatik dan Paradigmatik Bahasa Al-Qur’an - Amin, Nur Taqwa; Dekoz, Dedi Rochmad H. A.; Oktavera, Hasnil; Berti Arsyad (ELOQUENCE : Journal of Foreign Language, 2022)
Background: nterpreting the Qur'an, especially mutasyabihah verses, can be done by syntagmatic and paradigmatic analyses to obtain more detailed information about the meaning and derivations. Purpose: This study analyzes the linguistic and relational meanings of the word Al-yadd in the Qur'an. Method: This research is library research, with a content analysis approach to syntagmatic and paradigmatic aspects. Data were obtained from the redaction of the Qur'anic verses containing the word al-yadd in the form of mufrad, mutsanna, and jamak. The steps of analysisare carried out by a literature study, determining samples, categorization, coding and data processing, and analysis of meaning based on syntagmatic and paradigmatic approaches to determine the relational meaning of al-yadd in these verses. Results and Discussion: The results showed that the word Al-yadd in the Qur'an is mentioned 119 times and spread over 109 verses. In terms of quantity, the word al-yadd is in the form of three variants; singular 21 times, double 32 times, and plural 66 times; from these three variants, the word al-yadd forms many phrases with different meanings in each redaction. The lexical meaning of al-yadd is hand to humans and others. The relational meaning of the word al-yadd in the Qur'an varies greatly depending on the methods and approaches used in the analysis. Among the syntagmatic relational meanings of the term al-yadd are qudrah, power, in front, and the gift of grace. Its paradigmatic relational meanings are palm, arm, benefactor, and humble. Conclusions and Implications: This study concludes that the paradigmatic and syntagmatic approaches to the word al-yadd produce a variety of meanings so that the word should not be interpreted farially because each word must be seen in relation to the adjacent or accompanying words. This research implies that every word in the Qur'an does not only have one fixed meaning, so to find out the diversity of meanings, one of them must be analyzed with a paradigmatic and syntagmatic approach more comprehensively.